Non-linear Functional Brain Co-activations in Short-Term Memory Distortion Tasks - Ceglarek, Anna; Ochab, Jeremi K.; Cifre, Ignacio; Fafrowicz, Magdalena; Sikora-Wachowicz, Barbara; Lewandowska, Koryna; Bohaterewicz, Bartosz; Marek, Tadeusz; Chialvo, Dante R. (Frontiers in Neuroscience, 2021)
Recent works shed light on the neural correlates of true and false recognition and the influence of time of day on cognitive performance. The current study aimed to investigate the modulation of the false memory formation by the time of day using a non-linear correlation analysis originally designed for fMRI resting-state data. Fifty-four young and healthy participants (32 females, mean age: 24.17 ± 3.56 y.o.) performed in MR scanner the modified Deese-Roediger-McDermott paradigm in short-term memory during one session in the morning and another in the evening. Subjects’ responses were modeled with a general linear model, which includes as a predictor the non-linear correlations of regional BOLD activity with the stimuli, separately for encoding and retrieval phases. The results show the dependence of the non-linear correlations measures with the time of day and the type of the probe. In addition, the results indicate differences in the correlations measures with hippocampal regions between positive and lure probes. Besides confirming previous results on the influence of time-of-day on cognitive performance, the study demonstrates the effectiveness of the non-linear correlation analysis method for the characterization of fMRI task paradigms.